EKSISTENSI TANAH BENGKOK SETELAH BERUBAHNYA PEMERINTAH DESA MENJADI PEMERINTAH KELURAHAN (STUDI KASUS DI WILAYAH KELURAHAN KELAPA DUA DAN KELURAHAN BENCONGAN, KECAMATAN KELAPA DUA, KABUPATEN TANGERANG) - Syihabudin Sya’ban S.P.; Hanafi Tanawijaya (Fakultas Hukum Universitas Tarumanagara, 2019)
Land the village treasury as assets of village growing based on tradition or customs living in communities. The twisted now called the village or official known as land use village, the twisted is old term born and developed in the community Java or Bengkok Village, formally known as the rights of use. Status village fights of use to the local government assets when the status of his rule chage from village into kelurahan. When turned into autonomous region district be automatically village asset to be an local governments. When village status turned info village the assets rurn into local government owned by the village and released earlier. The twisted is a village asset used to substitute salary and given as payment for village officials. After the village government to kelurahan, and so the twisted could not be us as wages. This happened in urban village Kelapa Dua and urban village Bencongan.